Implementation and validation of a Ground Source Heat Pump model in MATLAB - Casetta, Damien (My University, 2012)
The aim of the project is the implementation of a simple Ground-Source Heat Pump (GSHP) system model in MATLAB. The program is able to run multi-year simulations for a given building hourly load profile, with an hourly time step. The GSHP system, including borehole heat exchanger geometry, borehole field configuration, circulating uid properties, heat pump selection, can be set up to simulate typical installations. The system model itself consists of an analytical borehole heat exchanger model and of a water-to-water heat pump model based on catalog data. Both components are coupled though a set of equations solved iteratively within a time step, with a robust and efficient MATLAB built-in solver. A procedure aggregation of hourly building load values is also implemented. The implemented GSHP system model is compared with an equivalent reference model in TRNSYS. It has been developed for validation purposes and a control strategy has been included in order to obtain two models with a similar operation. Both models gives average Coefficient of Performance (COP) and average uid temperature with a difference of less than 2%. The MATLAB environment has been chosen as a universal and widely spread tool among engineers. The code is meant to be simple and easy to use.
Keywords: Energi; Byggnadsteknik; Hållbar utveckling; Building Futures; Energy; Building engineering; Sustainable Development; Building Futures